INVENTARISASI JENIS BURUNG PANTAI DI KAWASAN PULAU MARSEGU KABUPATEN SERAM BAGIAN BARAT PROVINSI MALUKU - Billy Seipalla (Lambung Mangkurat University-Indonesia, 2020)
This research was conducted on the island of Marsegu because this area is included in the area of the natural marine tourism park which should be the concern of the government and the community around the island. The study aimed to determine the species of shorebirds found in the Marsegu island region in the western part Seram. The study was conducted in the morning and evening for 2 days at the location which is a gathering place for shorebirds. In the study location, 8 species of shorebirds were found and then inventoried and identified. The number of shorebirds species found in the Marsegu island area was 8 species, among others; Coral egrets (Egratta sacra), Big Egrets (Egretta alba), Trinil Beach (Actitis hypoleucos), Little sea worms (Sterna albifrons), Black wing sea worms (Sterna fuscata), Big (Fregata minor), Sea-eagle belly white (Haliaetus leucogaster), Bondol Hawk (Indus Haliastur), with the dominant species being the Big Cingkalang (Fregata minor). The most common species are large Cikalang (minor Fregata), small sea virgin (Sterna albifrons), and large egret (Egretta alba). Factors that cause the survival of shorebirds on the Marsegu island region because they store a lot of food supplies. In addition, food availability is affected by a lack of human activity in this region and the establishment of this area as a Marine Nature Tourism Park.